Effects of Spacers on Photoinduced Reversible Solid‐to‐Liquid Transitions of Azobenzene‐Containing Polymers. Issue 46 (25th July 2019) - Weis, Philipp; Hess, Andreas; Kircher, Gunnar; Huang, Shilin; Auernhammer, Günter K.; Koynov, Kaloian; Butt, Hans‐Jürgen; Wu, Si
Abstract: Photoisomerization in some azobenzene‐containing polymers (azopolymers) results in reversible solid‐to‐liquid transitions because trans ‐ and cis ‐azopolymers have different glass transition temperatures. This property enables photoinduced healing and processing of azopolymers with high spatiotemporal resolution. However, a general lack of knowledge about the influence of the polymer structure on photoinduced reversible solid‐to‐liquid transitions hinders the design of such novel polymers. Herein, the synthesis and photoresponsive behavior of new azopolymers with different lengths of spacers between the polymer backbone and the azobenzene group on the side chain are reported. Azopolymers with no and 20 methylene spacers did not show photoinduced solid‐to‐liquid transitions. Azopolymers with 6 or 12 methylene spacers showed photoinduced solid‐to‐liquid transitions. This study demonstrates that spacers are essential for azopolymers with photoinduced reversible solid‐to‐liquid transitions, and thus, gives an insight into how to design azopolymers for photoinduced healing and processing. Abstract : In the spotlight : The influence of the spacer (R in the figure) on photoinduced solid‐to‐liquid transitions of azopolymers is investigated. Whereas azopolymers with moderate spacer length exhibit photoinduced solid‐to‐liquid transitions, azopolymers with short and long spacers do not. Healing scratches with light is demonstrated on hard coatings made from azopolymers and followed in real time.